Fire effects on soils - A pilot scale study on the soils affected by wildfires in the Czech Republic - Martínez Barroso, Petra; Vaverková, Magdalena Daria (Polish Society of Ecological Engineering, 2020)
Fires have always been a natural component influencing ecosystems and driving their evolution; however, in recent years they have become too frequent and ecosystems are not able to cope with them anymore. Fires destroy the natural vegetation, which prevents the soil erosion, and affect the soil properties which delay the natural recovery of the fire affected area. This experiment was conducted to assess the phytotoxicity of fire affected soil and to investigate whether different soil amendments can help to decrease the negative effect of fire on soil properties. The study utilised the PhytotoxkitTM test. The tested burnt soil was supplemented with 3% w/w of the following individual soil amendments: bentonite, biochar, compost and diatomite. Then, the phytotoxicity tests were carried out with garden cress (Lepidium sativum L.) and white mustard (Sinapis alba L.). The pH and electrical conductivity of soil were measured and it was revealed that the individual soil amendments affected the values of pH and electrical conductivity diversely. The highest root growth stimulation for Sinapis alba L. was observed when diatomite was added, whereas the most favourable amendment for the stimulating root growth of Lepidium Sativum L. were compost, diatomite and biochar, respectively. This study recommended repeated testing for the amendments that show a capability to stimulate the root growth and conducting tests on a wider group of plant species.
Keywords: Effects on soil properties; Lepidium Sativum L.; Phytotoxicity; Preliminary testing; Sinapis Alba L.; Soil amendments; Wildfire